Il disagio psichico perinatale - Anna Pompili (Il sogno della farfalla, 2019)
In United Kingdom, during the perinatal period nearly a quarter of maternal deaths is related to mental health. Pregnancy, delivery and post partum may be conditions of psychological susceptibility, worsened by hormonal changes and cultural environment. During pregnancy and perinatal period, women have to face stereotyped models inspired by religion and by a pseudo-scientific idea of maternal instinct and motherhood. The mismatch between women’s feelings and these models can cause or contribute to the onset of perinatal psychic disorders. Early detection of women and couples at risk is fundamental for early treatment, in order to reduce risks. Nevertheless, promoting a real knowledge of the physiology of pregnancy, birth and puerperium can knock down false, pathogen stereotypes.